A MultiCriteria Group Decision Support System for Industrial Diagnosis - Djamila, Hamdadou; Libourel, Thérèse (INFOCOMP Journal of Computer Science, 2011)
The diagnosis is a research key element to improve business performance. However, the diagnosis methods do not possess a unique and universal aspect in a context where diagnosis diversity and complexity are increasing. Thus, there is, currently, no susceptible diagnosis method which ensures the relevance, efficiency and effectiveness of maintenance in all circumstances. The work presented in this article aims to eliminate or at least lessen the impact of unsuccessful attempts of the diagnosis tools development on the good functioning of a company. The development of the multicriteria group decision support system for diagnosis assistance (DIAG-GDSS) is an answer to the problem; it is a collective decision-making tool for the choice of the most relevant diagnosis method. On the basis of a set of criteria and diagnosis methods, carefully selected and implemented , the developed tool allows: • to assist decision makers in maintenance, according to their preferences often conflicting, to adopt a diagnosis method; • to make a quick and efficient diagnosis using the developed methods. In order to meet this group decision where different viewpoints are considered, we propose a multilateral negotiation protocol, coupled with a multicriteria method namely ELECTRE III. This protocol features a coordinator agent and a set of participating agents, trying to find a compromise that best meets all the decision makers.